2012
DOI: 10.2147/ijn.s34127
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles and their potential for application in bone

Abstract: Abstract:Biomaterials are commonly applied in regenerative therapy and tissue engineering in bone, and have been substantially refined in recent years. Thereby, research approaches focus more and more on nanoparticles, which have great potential for a variety of applications. Generally, nanoparticles interact distinctively with bone cells and tissue, depending on their composition, size, and shape. Therefore, detailed analyses of nanoparticle effects on cellular functions have been performed to select the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
138
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(139 citation statements)
references
References 148 publications
(231 reference statements)
0
138
0
1
Order By: Relevance
“…1 TiO 2 NPs, when added to composites, increase their durability to mechanical damage, especially cracking and breaking, and minimize the risk of bacterial infections. [1][2][3] Because of these unique properties TiO 2 NPs are increasingly used in endoprostheses and scaffolds for bonetissue reconstruction. 2,3 However, nanotoxicological studies are crucial for the safe and sustainable development of emerging and established nanomaterials such as TiO 2 NPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 TiO 2 NPs, when added to composites, increase their durability to mechanical damage, especially cracking and breaking, and minimize the risk of bacterial infections. [1][2][3] Because of these unique properties TiO 2 NPs are increasingly used in endoprostheses and scaffolds for bonetissue reconstruction. 2,3 However, nanotoxicological studies are crucial for the safe and sustainable development of emerging and established nanomaterials such as TiO 2 NPs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Because of these unique properties TiO 2 NPs are increasingly used in endoprostheses and scaffolds for bonetissue reconstruction. 2,3 However, nanotoxicological studies are crucial for the safe and sustainable development of emerging and established nanomaterials such as TiO 2 NPs. Indeed, TiO 2 NPs may also have harmful/cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…127,128 To monitor these pro cesses, hMSCs have been labeled with diverse NPs such as quantum dots (QDs), fluorescence-labeled mesoporous silica NPs, gold NPs, and superparamagnetic iron oxide (SPIO) NPs. 7 The fluorescent labeling of osteoblast cells using HA grown with nucleating seed of hydrophilic CdSe/ ZnS QDs allows real-time observation of cell under confocal microscope. A study performed on MC3T3-E1 osteoblast cells showed that the cells could engulf HA with surfacetailored QDs showing fluorescent spots in the cytoplasm, while HA and QDs NPs were not engulfed.…”
Section: Diagnosismentioning
confidence: 99%
“…6 Many studies have shown that nanomaterials enable enhancement of osteointegration and promote healing of bone-related diseases. 7 Wang et al 8 have recently shown that nanostructured calcium phosphate scaffolds could support stem cell attachment/proliferation and induce osteogenic differentiation due to their chemical or crystallographic similarities to inorganic components of bone. Antimicrobial and drug-eluting coatings are other examples for the application of nanomaterials in orthopedic medicine.…”
Section: Introductionmentioning
confidence: 99%
“…7 Nanoparçacıkların kemikteki kullanım alanlarının başında rejeneratif tedavide hücre işa-retleyici, kanser ve diğer kemik hastalıklarında ilaç taşıyıcı ve gen taşıyıcı, kemik doku mühendisliğinde ise mineralizasyonu aktive etmek için kaplama ve dolgu maddesi olarak kullanımı gelmektedir. [7][8][9] Nanoparçacıkların günlük yaşamda kullanım-larına ilişkin çalışmaların artışına paralel olarak, bu parçacıkların insan ve çevre sağlığı üzerine etkilerine ilişkin araştırmalar da giderek artmaktadır. Doğal ortamda veya kullanılan ürünlerde bulunan nanoparçacıklar bulundukları ortamdan kolaylıkla ayrılarak havaya, havadan da solunum yoluyla vü-cuda geçmektedirler.…”
unclassified